T-way test data generation startegy with MBO algorithm - Hasneeza, L. Zakaria; Kamal Z., Zamli (2015)
This paper presented the implementation of a nature inspired metaheuristic search algorithms that are Migrating Birds Optimization (MBO) algorithm and Genetic Algorithm (GA) hybrid to a t-way test data generation strategy. The proposed strategy is called improved MBO Testing Strategy (iMTS). Based on the published benchmarking results, the result of these strategies is competitive with most existing strategies in terms of the generated test size in many of the parameter configurations. For a higher strength, iMTS is able to produce a minimum test suite size. In the case where these strategies are not the most optimal, the resulting test size is sufficiently competitive. The strategy serves as our research conduit to investigate the effectiveness of MBO algorithm for t-way test data generation strategy